Catholic Economics : Alternatives to the Jungle - Sibley, Angus (Book collections on Project MUSE., 2015)
Inequality, unemployment, degradation of our environment: these and other practical economic problems reflect faulty economic theories. We have been led astray by ideas that made some sense in the past but are unsuited to our times and by ideas that are fundamentally mistaken. The Catholic Church has an extensive body of teachings on economic and social matters, too little known even among Catholics, which offers practical alternatives to the economics of the jungle. This book provides clear explanations of major errors in conventional economic thinking and shows how the church's teachings can point us in a better direction.